Information, networks, and the complexity of trust in commons governance. Issue 2 (2011) - Henry, Adam Douglas; Dietz, Thomas
The publication of Elinor Ostrom's (1990) Governing the Commons fueled significant theoretical and empirical progress in the field of commons governance and collective action, most notably in the form of the Institutional Analysis and Development (IAD) framework. A central question within this literature is how trust is created, maintained, and potentially destroyed in the context of sustainability issues. While the commons literature has provided a deeper understanding of trust, most empirical work has been done in relatively simple settings that do not capture the complexity of many global, institutionally-complex dilemmas that we face today. This paper discusses how our understanding of trust in these more complex settings may be improved by considering how two broad categories of variables – belief systems and networks – influence trust.